Impact of E-Learning on Pupils Academic Performance in Social Studies: A Case Study of Selected Schools in Ikumba Sub-County Rubanda District. - Tibekyinga, William (Kabale University, 2024)
The study focused on the impact of e-learning on pupils' academic performance in social studies in schools in Ikumba sub-county, Rubanda district. The study followed research objectives, which were to find out the role e-learning plays on pupils' academic performance in social studies, identify major problems affecting the use of e-learning on pupils' academic performance in social studies, and propose potential strategies for improving the use of e-learning on students' academic performance in social studies. The research was conducted using a descriptive research design and included both qualitative and quantitative data. A sample size of 80 respondents was drawn from schools in the Rubanda district's lkumba sub-county. The findings of the study revealed that female respondents were highly represented in the study by 71 %; married respondents were also highly represented by 64%; and 27% show that training both teachers and pupils is among the major roles of e-learning in schools. The recommendations of the study included the following: E-learning is here to stay and can make a much stronger contribution to higher education in the years to come. However, there are some negative effects of online learning, as it does not offer real face-to-face contact and interaction with teachers and imposes a time commitment and less accountability on pupils. There are also many online struggles that students face, such as the impossibility to stay motivated all the time, as they sometimes feel that they are completely isolated. In addition, teachers feel powerless to control students' cheating or impose classroom discipline. In addition to that, poor students struggle o get the necessary electronic equipment to access this new mode of learning, interact in due time with their teachers, make necessary comments and raise questions to clear ambiguities and any equivocal statements, and get appropriate feedback from their teachers.